Personality determinates of religious feelings among higher education students - Głaz, Stanisław (Studia Psychologica: Theoria et praxis, 2006)
The author of the article interested in the relationship of personal characteristics and religious feelings towards God, tried to answer the following questions: Do the independent variables . gender and discipline studied, affect: personal traits and feeling of anxiety towards God? Which, how much and in what order, do the independent variables relating to personality traits, explain the variance of dependent variables relating to religious feelings? In the research the following surveying tools were used: To describe the five dimensions of a personality, the McCrae and Costa .Big Five. test was used. The Szymołon.s Scale of Anxiety and Fascination was used to describe the feelings towards religious feelings and God and the multi step regression analysis. The research was carried out in 2002. It encompassed 134 students between the age 19-21 years old, all the participants were experiencing God.s presence/absence. Both men and women showed similar personal characteristics traits. The most developed of those were: conscientiousness, conciliatory and extrovertic attitude. The feelings of fascination about God and the .filial fear. towards Him, were very strong among female pedagogy students but very weak among female forestry students. Male theology students showed the highest .slave fear. towards God, and the male philosophy students the lowest. The strongest personality trait having an effect on religious feelings among female students was openness to experiences, and among males it was conscientiousness.